Lectures on the geometry of Poisson manifolds - Vaisman Izu (Basel Birkhauser Verlag, 1994)
The book aims to provide the reader with a monograph that enables to study systematically basic & advanced material on the recently developed theory of Poisson manifolds & that also offers ready access to bibliographical references for the continuation o
Keywords: Poisson manifolds